Business groups in developing capital markets: Towards a complementarity perspective. (8th July 2014) - Chittoor, Raveendra; Kale, Prashant; Puranam, Phanish
<x xml:space="preserve">Abstract</x> Prior research suggests that business groups (BGs) in developing economies have emerged as alternatives to poorly developed economic institutions in these countries. In this paper, we argue that this does not imply they are always substitutes. Specifically, we consider the case of capital markets, a key economic institution: while the absence of well‐developed capital markets may indeed have stimulated the emergence of business groups, we propose that BG affiliation and the scrutiny that maturing capital markets impose on firms that participate actively in them nevertheless can play a complementary role in influencing a firm's performance. We find support for our predictions in a novel longitudinal data set of Indian firms that contain both listed and unlisted BG affiliated as well as unaffiliated firms. Copyright © 2014 John Wiley & Sons, Ltd.